Upper Semicontinuity of Pullback Attractors for the 3D Nonautonomous Benjamin-Bona-Mahony Equations - Xinguang Yang; Xiaosong Wang; Juntao Li; Lingrui Zhang (The Scientific World Journal)
We will study the upper semicontinuity of pullback attractors for the 3D nonautonomouss Benjamin-Bona-Mahony equations with external force perturbation terms. Under some regular assumptions, we can prove the pullback attractors 𝒜ε(t) of equation ut-Δut-νΔu+∇·F→(u)=ɛg(x,t), x∈Ω, converge to the global attractor 𝒜 of the above-mentioned equation with ε=0 for any t∈ℝ.